The Tradition of Redeeming Twin Children of Newlyweds - Rahmadi Agus Setiawan; Nur’aini; Hidayatun Ulfa; Ouedraogo Saidou (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2025)
This study examines the Tebus Anak Kembar Pengantin tradition practiced in Kertosari Village, Jumo District, Temanggung Regency, from the perspectives of Islamic law and local custom (‘urf). Employing a qualitative approach with a socio-legal method, the research is based on field data collected through interviews, observation, and documentation involving community leaders, religious figures, and local residents. The findings reveal that the tradition is a form of living local wisdom rooted in Javanese culture, carried out through symbolic rituals such as family deliberation, collective prayers, the symbolic transfer of redemption money, and child caregiving by an adoptive family. Sociologically, the practice aims to strengthen kinship ties, maintain social harmony, and promote collective responsibility in child upbringing. From an Islamic legal perspective, the tradition is acceptable insofar as it is understood as kafālah (child guardianship) rather than a transaction involving the sale of a child, as it does not alter lineage (nasab) and emphasizes intentions oriented toward public benefit (maṣlaḥah). Within the framework of ‘urf, the tradition may be classified as ‘urf ṣaḥīḥ, provided that it does not contradict sharīʿah principles. However, the study also identifies challenges related to Indonesian positive law, particularly the absence of formal adoption procedures, which may result in legal uncertainty regarding the child’s status. Therefore, the study underscores the need for legal awareness and guidance to harmonize the preservation of local tradition with the principles of Islamic law and child protection